Does deforestation endanger energy security? A panel GMM evidence from 47 sub-Saharan African countries - Ofozor, Christopher Amechi; Abdul-Rahim, A.S.; Chin, Lee; Bani, Yasmin; Sulaiman, Chindo (Springer, 2024)
This empirical study investigates the impact of deforestation on energy security in sub-Saharan Africa. To achieve this, we explored the intricate dynamics between deforestation, key energy security indicators, and socio-economic factors in sub-Saharan Africa. We employed a comprehensive dataset and analysed it with system GMM methodology and difference GMM and pooled OLS as robustness checks. The study validates the model’s suitability and confirms a significant negative relationship between deforestation rates and energy security. A central finding is the consistently negative impact of deforestation on energy security across various models. Diminishing forest cover is shown to jeopardise a nation’s ability to meet energy demands, underscoring the urgent need for policies promoting forest conservation and sustainable management. The study also identifies positive associations between energy security and total primary energy supply, per capita energy consumption, carbon dioxide emissions, and renewable energy. Higher energy supply and consumption and increased reliance on renewables contribute to enhanced energy security. However, unchecked population growth is highlighted as a potential impediment. Policy implications advocate for comprehensive interventions, emphasising conservation strategies, renewable energy adoption, and population management. It also calls for foreign trade policies that emphasise timber certification and sustainability agreements to protect forest resources alongside regional security measures and collaborative guidelines for sustainable forest management. The findings provide a nuanced understanding for policymakers, offering a roadmap to navigate challenges and opportunities in pursuing sustainable and secure energy systems in sub-Saharan Africa.